FTIR spectroscopic semi-quantification of iron phases: A new method to evaluate the protection ability index (PAI) of archaeological artefacts corrosion systems. (1st April 2018) - Veneranda, Marco; Aramendia, Julene; Bellot-Gurlet, Ludovic; Colomban, Philippe; Castro, Kepa; Madariaga, Juan Manuel
Highlights: A new iron corrosion semi-quantification method is proposed. A homemade decomposition software (PALME) was used to treat Fourier Transform Infrared Spectroscopy (FTIR) spectra. This approach was applied for the study of both, mixtures of pure iron phases and real archaeological corrosion samples. Fast, reliable and repetitive results were reached using extremely small quantity of material (below 0.5 g). Abstract: This study proposes an innovative approach to semi-quantify the main iron corrosion phases found in corrosion systems of archaeological artefacts. This method is based on the treatment of Fourier Transform Infrared Spectroscopy (FTIR) data using a homemade spectra decomposition software (PALME). Its application was first tested on mixtures of pure iron corrosion standards. After optimization, it was used to study real archaeological samples and evaluate the stability of their corrosion system. Considering that reliable and repetitive results were reached using extremely small quantities of material, this method can be particularly suitable for the study of iron-based objects of cultural interest.